DEVELOPING ENGLISH COURSE BOOK FOR SECOND GRADE KINDERGARTENERS - Lely Silia Wardhani; Mohammad Adnan Latief; Yazid Basthomi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2017)
This study is aimed to develop English course-book for second grade of kindergarten. The method used in this study is Research and Development (R&D). The steps of this study consist of needs analysis, material development, expert validation, first revision, try out, second revision, and final product. The result of this study indicates that the developed product is applicable for young learners. Additionally, the product is attractive and fun to be used.Penelitian ini bertujuan mengembangkan buku pelajaran Bahasa Inggris bagi siswa tingkat dua Taman Kanak-kanak. Metode yang digunakan dalam penelitian ini adalah Research and Development (R&D). Langkah-langkah yang digunakan dalam penelitian ini melingkupi analisis kebutuhan, pengembangan materi, validasi ahli, revisi pertama, uji coba, revisi kedua, dan hasil produk. Hasil penelitian ini menunjukkan bahwa produk yang telah dikembangkan mudah digunakan oleh pembelajar usia dini. Sebagai tambahan, produk ini juga menarik dan menyenangkan.